Schiff base metal derivatives enhance the expression of HSP70 and suppress BAX proteins in prevention of acute gastric lesion - Golbabapour, S.; Gwaram, N.S.; Al-Obaidi, M.M.J.; Soleimani, A.F.; Ali, H.M.; Majid, N.A. (Hindawi Publishing Corporation, 2013)
Schiff base complexes have appeared to be promising in the treatment of different diseases and disorders and have drawn a lot of attention to their biological activities.This study was conducted to evaluate the regulatory effect of Schiff base metal derivatives on the expression of heat shock proteins (HSP) 70 and BAX in protection against acute haemorrhagic gastric ulcer in rats. Rats were assigned to 6 groups of 6 rats: the normal control (Tween 20 5% v/v, 5 mL/kg), the positive control (Tween 20 5% v/v, 5 mL/kg), and four Schiff base derivative groups named Schiff 1, Schiff 2, Schiff 3, and Schiff 4 (25mg/kg). After 1h, all of the groups received ethanol 95% (5 mL/kg) but the normal control received Tween 20 (Tween 20 5% v/v, 5 mL/kg). The animals were euthanized after 60 min and the stomachs were dissected for histology (H&E), immunohistochemistry, and western blot analysis against HSP70 and BAX proteins.The results showed that the Schiff base metal derivatives enhanced the expression of HSP70 and suppressed the expression of BAX proteins during their gastroprotection against ethanol-induced gastric lesion in rats.